Argument Properties for a Class of Analytic Functions Involving Libera Transform. (3rd November 2016) - Alkahtani, Badr S.; Bulboacă, Teodor; Kumar, Rakesh; Alqahtani, Rubayyi
Abstract : The purpose of this paper is to find sufficient argument properties, such that the images of some subclasses of functions by the Libera transform have bounded arguments.